2020
DOI: 10.1108/jfc-11-2019-0147
|View full text |Cite
|
Sign up to set email alerts
|

Risk management, top management support, internal audit activities and fraud mitigation

Abstract: Purpose This paper aims to examine the effect of top management support (TMS) and risk management (RM) on the internal audit activities (IAA) and fraud mitigation (FM) in the Libyan banking sector. Design/methodology/approach The data is collected using a survey questionnaire of 16 commercial banks in Libya and analysed using a structural equation modeling. Findings The study shows positive and significant relationships between RM and employees’ FM and TMS and employees’ FM. The study also demonstrates a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…This means that the higher the level of organizational risk management is, the higher the organization's fraud awareness is. This finding supports the results of studies conducted by Hess and Cottrell (2016) and Alazzabi et al (2020) who found that preventing fraud and developing fraud awareness took more than 1 year, thus requiring risk management in the organization's operational activities.…”
Section: Discussionsupporting
confidence: 89%
“…This means that the higher the level of organizational risk management is, the higher the organization's fraud awareness is. This finding supports the results of studies conducted by Hess and Cottrell (2016) and Alazzabi et al (2020) who found that preventing fraud and developing fraud awareness took more than 1 year, thus requiring risk management in the organization's operational activities.…”
Section: Discussionsupporting
confidence: 89%
“…For a banking institution fraud risk has become crucial facet of risk management system (Dorogovs et al , 2013; Agarwal and Sharma, 2014; Alazzabi et al , 2020). Dabari and Saidin (2014) and Tandon and Mehra (2017) concluded that effective risk management practices improved the organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sy and Tinker (2019); Fernández-Laviada (2007); and Kabuye et al (2019) further stated that internal auditors preform the detailed investigation on effectiveness of internal control system and risk management practices implemented by the banking institution and provide their assurance on it. Risk management, adequate top management support and internal auditing activities are vital factors for effective fraud management in an organization (Dabari and Saidin, 2014; Kabuye et al , 2019; Alazzabi et al , 2020), e.g. independent internal auditors who have adequate knowledge, dexterity and experience and have enough top-management support, can help the management in a better way in establishing efficacious anti-fraud mechanisms in financial services sector (Kabuye et al , 2017; Alazzabi et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Within an informational security context, top management support signals the importance of information security to the organization 42 including relevant sanctions to ensure ISP achieving its intended outcomes. 36 In the literature, top management support is confirmed an imperative factor for various organizational initiatives such as the implementation of IS, 43,44 fraud mitigation, 45 and IS security issues. 40,46,47 This support may take the form of guidance or participation in those activities, and more importantly, top management support can secure adequate resources for relevant initiatives to take place.…”
Section: Research Model and Hypothesis Formulationmentioning
confidence: 99%